Transcript-Based Lesson Analysis: Reward and Punishment Using Wordwall.net Toward Students’ Self-Efficacy in Learning Excretory System - Muharam, Ghevira Syaharani Aulia; Eliyawati , E.; Prima, Eka Cahya; Risnawati, Ika (Universitas Negeri Semarang, 2024)
Among the many things that can improve learning, self-efficacy gives a careful thought, especially in difficult subjects like science. This study aims to analyze the effect of reward and punishment system using Wordwall.net on students' self-efficacy in learning excretory system by using Transcript Based Lesson Analysis. This study used descriptive method conducted in a private school in Bandung. The data was collected through direct observation then will be analyzed based on observation sheet, the teachers' lesson plan, questionnaire, but mainly using the documentation from videos and voice recording to conduct the transcript-based lesson analysis. The results shows that rewarded students have higher engagement and involvement in the teaching and learning process, as well as the higher average value which is 68% categorized as good. In contrast, punished students have lower engagement and involvement in the teaching and learning process, as well as the lower average which 37% categorized as poor. However, the value of Pearson correlation is 0.065 which averages there is no significance correlation between. Thus, reward and punishment system still can be implemented in science learning even there is no correlation between reward and punishment system toward students' self-efficacy since there is still a positive impact towards students' self-efficacy as well as participation.